TYPES OF BARRIERS TO COMMUNICATION IN EMERGENCY ROOM BETWEEN NURSE AND PATIENT’S FAMILY IN DOLOKSANGGUL HOSPITAL - Evi . Aisyah; Meisuri . .; Fauziah Khairani Lubis (Universitas Negeri Medan, 2023)
The objective of this study was to describe types of barriers to communication in emergency room between nurse and patient’s family in Doloksanggul hospital. This research was conducted by using descriptive qualitative research. The data of this study were utterances in conversation between nurse and patient’s family in Doloksanggul hospital. Participant observation technique was performed to collect the data. The results showed that (1) The types of communication barriers most frequently encountered in emergency room of the Doloksanggul Hospital 4% related to process barriers, 32 % related to semantic barriers, 1 % related to physical and cultural barriers, 12% related to psychological barriers, and 16 % related to perception. Then, the dominant type is related to psychological barriers. From the analyzed realization types of barriers to communication it was found that Psychological barriers was the largest number, it showed that unstable mental condition or panic because of the patient's family situation who worried about the patient create barrier to communication.